1990
DOI: 10.1093/oxfordjournals.humrep.a137168
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-sperm antibodies in serum, seminal plasma and cervical mucus by the immunobead test

Abstract: Anti-sperm antibodies in serum and seminal plasma were detected by means of an indirect immunobead test (IBT). Immunobeads with separate specificites for each immunoglobulin class (IBT-IgG, IBT-IgM, and IBT-IgA) were used. Semen parameters were controlled in all sperm donors and Biggers-Whitten-Whittingham (BWW) medium supplemented with human serum albumin (HSA) was used to increase sperm motility. This technique was tested with high titre anti-human sperm sera induced in rabbits. Sperm tails showed a good res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Once the barrier is broken immune cells are able to detect the presence of sperm due to their unique antigen surface (Andolz et al, 1995), this triggers a response by the immune system to treat sperm as an "invader" and attack it, antibodies then attach themselves to different parts of the sperm and interfere with male fertility in a number of ways (Ayvaliotis et al , 1995) antibodies that are located on the tail of sperm can cause the sperm to become immobilized or clump together (Collins et al, 1993), when antibodies are found on the head of sperm they can prevent the sperm from being able to efficiently make its way through a woman's cervical mucus to the egg , however it is also possible for a woman to develop antisperm antibodies in her cervical mucus, which will serve to hinder attempts at conception even more (Jarow et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Once the barrier is broken immune cells are able to detect the presence of sperm due to their unique antigen surface (Andolz et al, 1995), this triggers a response by the immune system to treat sperm as an "invader" and attack it, antibodies then attach themselves to different parts of the sperm and interfere with male fertility in a number of ways (Ayvaliotis et al , 1995) antibodies that are located on the tail of sperm can cause the sperm to become immobilized or clump together (Collins et al, 1993), when antibodies are found on the head of sperm they can prevent the sperm from being able to efficiently make its way through a woman's cervical mucus to the egg , however it is also possible for a woman to develop antisperm antibodies in her cervical mucus, which will serve to hinder attempts at conception even more (Jarow et al, 2002).…”
Section: Introductionmentioning
confidence: 99%